Origin of students’ sector within Ukrainian youth movement in 1917. - Khoroshev, Olexander (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences)
This article deals with problems of the organizational structure of student unions after the autocracy overthrow in 1917. It focuses on the factors which influenced the emergence and formation of student organizations. The article also gives a detailed analysis of the reasons of their variety, large scale and developmental multi-orientation according to both political goals and organizational principles. It describes specific conditions of activity of the young students’ generation during the transitional period of 1917. This period was characterized by conservatism in the organization of the studying process on the one hand and by the introduction of the advanced theories of scientific and social development on the other hand.